Construction of Formability Limit Curves for Low-Carbon Steels Used in the Manufacture of Pressure Cylinders - Barbosa Jaimes, Jhon Erikson; García-Paez, Ismael Humberto; Casadiego-Peralta, Claudia Liliana (Ingeniería, 2023)
Context: The aim of this study is to determine the formability of SG295 (2,2 mm thick) and SG325 (2,3 mm thick) steel sheets, as well as their relationship with the sheets’ behavior in deep drawing and stretching operations. To this effect, chemical, metallographic, and mechanical analyses of the sheets were carried out. Method: The chemical analysis was carried out via optical emission spectrometry, and the metallographic structure was analyzed using the ASTM E3 standard. The intrinsic properties related to the formability of materials such as the elongation to fracture for a 50 mm gauge length, the conventional yield limit at 0,2% elongation, the ultimate strength, the strain hardening exponent, and the anisotropy coefficient at 15% elongation were determined through tensile tests according to ASTM E8M, ASTM E646, and ASTM 517. Forming limit curves were determined under ASTM E2218, for which a device was designed, built, and attached to a universal testing machine. Results: The results for the SG295 and SG325 steel sheets were as follows: tensile strength; 450 and 520 MPa; elongation at fracture: 24,9 and 17,2%; strain hardening exponent: 0,24 and 0,19; normal anisotropy: 1,64 and 1,29; planar anisotropy: 0,23 and -0,02. The FLD0 determined from the formality limit curves (FLCs) for the two steel sheets showed ε1 values of 0,281 and 0,336, respectively. Conclusions: Although the intrinsic properties (such as A50, n, and rm) of the SG295 steel sheet show values related to a greater formability, the FLCs show that SG325 steel performs slightly better due to its greater thickness.